Charlie the Ranch Dog: Charlie's Snow Day - Ree Drummond (New York, United States HarperCollins Publishers Inc, 2014)
Ree Drummond (also known as The Pioneer Woman) and Charlie the Ranch Dog return in this snow-filled I Can Read title. When Charlie wakes up to a world covered in snow, he can't wait to go outside. He even takes a break from patrol duty to go sledding with his friends Walter and Sister. But when Walter goes missing, it's up to Charlie to take control of the situation and bring his buddy back. Charlie the Ranch Dog stars in bestselling author Ree Drummond's I Can Read title, just right for reading on your own snowy day! Charlie's Snow Day is a Level One I Can Read book, which means it's perfect for children learning to sound out words and sentences.
Keywords: Level Reader -- Level Reader